Propuesta de ruta agroturística como aporte al desarrollo del sector turístico del cantón Quilanga, provincia de Loja - Gaona Flores., Nayelly Elizabeth (2023)
Quilanga is a canton that belongs to the province of Loja, this has agrotourism farms that have diversity of natural and cultural attractions. Its territory presents climatic variations throughout the year which allows taking advantage of its natural resources, thus benefiting agrotourism within the canton. For this reason, the research work revolves around the theme "Agrotourism route proposal as a contribution to the development of the tourism sector of Quilanga canton, Loja province" and has as a general objective: to make the proposal of an agrotourism route as a contribution to develop the tourism of Quilanga canton, province of Loja; In the same way, three specific objectives were established: the first to carry out a diagnosis of the agrotourism farms in Quilanga, the second objective to design a route as an agrotourism product in Quilanga, and the third objective to determine the promotion plan for the agrotourism product. The methodologies applied were the following. For the first objective, techniques and tools were used, such as interviews adapted with different variables that include the methodology of the Tourism Valuation of Products with Territorial Identity (VPTI) and the Inter-American Institute for Cooperation on Agriculture (IICA) in order to diagnose its current state, surveys, summary sheets were from the Ministry of Tourism (MINTUR) to identify, classify, and prioritize the attractions to consider the route and graphic design tools that served to create the dissemination elements for the route; obtaining as results in the first specific objective the information of three competitors, the collection of information from seven farms which four were selected for the route. For the second objective it was determined that the tourist’s profile to acquire the product has an age range between 30 to 45 years, the elaboration of an itinerary for two days and the design of a brand for the route. Finally, the third objective was a promotion agenda by online communication, advertising and the development of social networks such as Facebook and Instagram, posters, flyers, etc. However, for the development of this proposal, the integrated work of public and private institutions such as the Decentralized Autonomous Government of Quilanga canton is recommended, as a local regulatory entity, which leads to satisfactory results among communities that can work training about tourist service as well as internal and external promotions of the sector.